2020
DOI: 10.5219/1294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of traditional fish processing methods on the proximate composition and ph of fish Black pomfret (Parastromateus niger)

Abstract: Fish is an important food in many Iranian diets. This is a good source of protein. Fish is the main source of animal protein in Iran. The effects of three different traditional processing methods (freezing, brining and frying) on nutritive composition of halva sia fish stored under ambient room conditions were determined. Fresh halva sia fish were obtained from Behbahan fish market. Cooking and processing techniques were carried out on fish Halva sia Parastromateus niger. The proximate composition of raw Paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(10 reference statements)
1
4
0
Order By: Relevance
“…The fish examined belonged to high protein (3.12%-17.51%). The low ash, fat, high protein, and moisture content values obtained from proximate analysis agreed with other analysis carried out by earlier researchers such as Effiong and Mohammed, 6 Mumba and Jose, 3 and Abdullahi. 11 In general, there are significant impacts of processing methods on proximate composition of fish.…”
Section: Macronutrients Contentsupporting
confidence: 89%
See 3 more Smart Citations
“…The fish examined belonged to high protein (3.12%-17.51%). The low ash, fat, high protein, and moisture content values obtained from proximate analysis agreed with other analysis carried out by earlier researchers such as Effiong and Mohammed, 6 Mumba and Jose, 3 and Abdullahi. 11 In general, there are significant impacts of processing methods on proximate composition of fish.…”
Section: Macronutrients Contentsupporting
confidence: 89%
“…Research work 6 showed that moisture content in fresh sample was affected brining process was decreased respectively (84.72% to 33.99%) with significant difference (P < .05), while protein, fat, ash, and energy values were affected, brining process were increased.…”
Section: Macronutrients Contentmentioning
confidence: 93%
See 2 more Smart Citations
“…Gelatin is derived from partial hydrolysis of fibrous structure of collagen. Collagen and gelatin are commonly found in bovine hide, pig skin or chicken waste, however, these sources have faced some constrains related to biological contaminants and religious issues [4]. Seafood processing wastes such as skin, bones, scales and fins are alternative sources for collagen and gelatin extraction.…”
Section: Introductionmentioning
confidence: 99%